Impact of Microcredit on Women’s Empowerment in Some Selected Villages in Bangladesh: Exploration of Change in Women’s Status and ‘Peace in the Family’ (Philosophy and Progress, 2021)
The empowerment of women has been a primary goal of microcredit programs in Bangladesh: but what empowerment is, or „should be‟, is contested terrain, as are causal relationships drawn between the implementation of microfinance and the empowerment of women. This paper explores the connection between microcredit and empowerment through analyzing data of a qualitative study. In this study data were collected from 98 adults (male=30; female=68) with age ranged from 18 to 56 years, through individual interviews, focus group discussions and participant observation for six months period of field work in three villages in Bogura, Bangladesh. The study elicited understandings of empowerment from women engaged in microcredit programs, as well as other members of their households. In the paper, we argue that exploring local contexts for, and meanings of, empowerment is crucial for assessing the criteria on which the success (or failure) of microcredit or empowerment is determined. We suggest that more sustained engagement with the local-level experience of empowerment may challenge assumptions about aims and objectives of empowering processes in development, and stand as a corrective to models of the empowered woman that may not acknowledge the extent to which empowerment is framed in, and by, social and relational dynamics and goals.Philosophy and Progress, Vol#63-64-; No#1-2; Jan-Dec 2018 P 29-64